Making the Most of the Cloud: How to Choose and Implement the Best Services for Your Library - Hastings, Robin (Rowman & Littlefield Publishers, 2013)
Cloud computing can be confusing - the number and types of services that are available through “the cloud” are growing by the day. Making the Most of the Cloud: How to Choose and Implement the Best Services for Your Library takes you through some of the more popular cloud services in libraries and breaks down what you need to know to pick the best one for your library. Some of the cloud services covered are: Email Integrated Library Systems (ILS) Backups Project Management Graphics Software and much more... With chapters covering cloud topics from the definition of a “cloud” to security in the cloud, this book will be beneficial for any library which is thinking of moving their services outside their organization.